Kandungan Gizi dan Daya Terima Donat dengan Penambahan Tepung Kacang Merah dan Tepung Ubi Banggai sebagai Kudapan Sehat untuk Ibu Hamil - Kamila KH Djiha; Nuristha Febrianti; Adillah Imansri (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2026)
Meeting the nutritional needs of pregnant women requires innovative strategies through the provision of healthy snacks with balanced nutritional value. Donuts are popular snack foods; however, they are generally made from wheat flour and have limited nutritional content. This study aimed to analyze the nutritional content and acceptability of donuts enriched with red bean flour and Banggai yam flour as a healthy snack for pregnant women. This experimental study employed a Completely Randomized Design (CRD) consisting of three formulations: F1 (35% red bean flour : 15% Banggai yam flour), F2 (40% : 10%), and F3 (45% : 5%), with two replications. Nutritional analysis included protein using the Kjeldahl method, fat using the Soxhlet method, and carbohydrate using UV-Vis spectrophotometry. Acceptability was evaluated using a hedonic test. Data were analyzed using ANOVA and the Kruskal–Wallis test. The results showed significant differences in protein, fat, and carbohydrate contents among formulations (p<0.05). The highest protein content was found in F3, the highest fat content in F2, and the highest carbohydrate content in F1. Acceptability did not differ significantly among formulations (p>0.05); however, F1 obtained the highest preference score. Donuts enriched with red bean flour and Banggai yam flour have the potential to be developed as a healthy local food–based snack for pregnant women.